Generation Z’s Response to YouTube Non-Skippable Ads: Exploring Determinants of Purchase Intention in Sri Lanka - Samarasinghe, Udakotuwa Gedarage Buddhika Darshani; Tennakoon, Weeramandappa Dewayalage Niranjala Shyamali Mendis; Sajeewani, Kamal Padmasiri Thakshila (Tecno Scientifica Publishing, 2025)
As digital media consumption continued to expand rapidly, non-skippable YouTube advertisements emerged as a significant medium for brands to reach the digitally native and influential Generation Z consumers. This study examined the influence of four dimensions, informational value, entertainment value, credibility, and irritation value, on the purchasing intentions of Generation Z consumers in Sri Lanka. Employing a quantitative research design, data were obtained through a structured questionnaire administered to 384 randomly selected YouTube users from a population of over 7.8 million active users in Sri Lanka. The collected data were analyzed using SPSS to evaluate the relationships among the four dimensions of advertising effectiveness and purchase intention. The overall findings supported the assertion that non-skippable advertisements could affect purchasing intentions. The entertainment dimension demonstrated the strongest positive influence on purchase intention, indicating that engaging and humorous advertisements effectively stimulated consumers’ buying decisions. The informational dimension also exerted a positive influence, suggesting that advertisements offering clear and relevant information aided consumers in the decision-making process. Interestingly, the irritation dimension also exhibited a positive relationship with purchase intention. Although irritation is generally perceived negatively, it may, when applied strategically, enhance memory retention and brand recall. Conversely, the credibility dimension showed a negative correlation with purchase intention in this context. The findings of this study provided valuable insights for marketers and brand strategists in developing non-skippable YouTube advertisements that integrate entertaining and informative elements capable of capturing consumer attention without generating excessive irritation. Such advertising strategies could contribute to the creation of stronger brand associations among Generation Z consumers in Sri Lanka.